Structural Identification of Products from the Chloromethylation of Salicylaldehyde - Kadwa, Ebrahim; Friedrich, Holger B.; Bala, Muhammad D. (Synlett, 2019)
In the functionalization of salicylaldehyde to give 5-(chloromethyl)salicylaldehyde, two byproducts [5-(hydroxymethyl)salicylaldehyde and 5,5′-methylenebis(salicylaldehyde)] were also isolated. Detailed characterizations and structural analyses of all three products by single-crystal X-ray diffraction, multinuclear NMR spectroscopy, high-resolution mass spectrometry, and IR spectroscopic techniques are presented and discussed. A strategy is presented for the preferential isolation of the two byproducts through column chromatography.
Keywords: salicylaldehyde; chloromethylation; chloromethylsalicylaldehyde; crystal structure; hydroxymethylsalicylaldehyde; methylenebissalicylaldehyde